ChemInform Abstract: Palladium‐Catalyzed Cross‐Coupling Reactions of Potassium N‐Methyltrifluoroborate Isoindolin‐1‐one with Aryl and Heteroaryl Chlorides. Issue 48 (2nd December 2014) - Nadaf, Rashid N.; Seapy, Dave G.
Abstract The title borate (III) undergoes Pd‐catalyzed Suzuki—Miyaura cross‐coupling with aryl and heteroaryl chlorides leading to N‐benzylisoindolin‐1‐ones under mild reaction conditions.